P1167Effect of diabetes on all-cause mortality in CRT patients. (18th June 2020) - Merkel, E D; Behon, A; Schwertner, W R; Pinter, A; Osztheimer, I; Geller, L; Zima, E; Becker, D P; Kosztin, A; Merkely, B
Abstract: Background: Heart failure patients with diabetes mellitus (DM) have a higher risk for all-cause mortality and also for sudden cardiac death. We lack data on the effect of adding an implantable cardioverter defibrillator (ICD) to cardiac resynchronization therapy (CRT) on all-cause mortality in diabetic heart failure patients. Purpose: We aimed to investigate the risk of DM on all-cause mortality in CRT patients, and to examine the beneficial effect of adding an ICD on all-cause mortality by left ventricular ejection fraction in CRT patients with or without DM. Methods: We examined retrospectively 2525 patients who underwent CRT implantation based on the current guidelines at our clinic between June 2000 and September 2018, of which 928 (36%) had diabetes. The primary endpoint was all-cause mortality, also expressed as events per 100 person-year by quintiles of ejection fraction (EF) with or without an ICD or DM. Time to event data was investigated by Kaplan Meier and multivariate Cox regressional analysis. Results: During our mean follow-up time of 4.6 years, 1432 (56%) patients reached the primary endpoint, of which 553 (38%) had DM. In the DM group, hypertension (82% vs. 66%; p‹0.01), ischemic etiology (56% vs. 44%; p‹0.01), myocardial infarction (43% vs. 36%; p‹0.01) was more frequent compared to non-DM group. There was no difference between the two groups regarding the implantation of an ICD (54% vs. 53%; p = 0, 84). Those with DM showed a 25% higher risk of all-cause mortality (HR 1.25; 95% CI 1.12-1.40; p‹0.01), also observable after adjusting for relevant clinical covariates such as age, gender, atrial fibrillation and the addition of an ICD (HR 1.17; 95% CI 1.06-1.31; p‹0.01). Examined as all-cause mortality per 100 person-year follow up, patients with EF›30% and DM (13, 7 events/ 100 person-year follow-up for an EF 30-35%) showed similar risk as those without DM and a severely impaired left ventricular function with EF‹25% (14 events/100 person-year follow-up for an EF <25%). Investigating the composite end-point of all-cause mortality and heart failure hospitalization, those with DM showed a 21% higher risk than non-DM CRT patients (HR 1.21; CI 1.09-1.34; p = 0 < 0.001). Adding an ICD for CRT patients with DM reduces the risk of all-cause mortality significantly by 32% (HR 0, 68; CI 0, 56 to 0, 82; p < 0.001) during the first six years but diminished on longer follow-up time. Conclusions: Diabetes was found as an independent predictor of all-cause mortality in CRT patients. Those with a left ventricular ejection fraction above 30% have comparable risk of mortality as non-diabetic patients with a severely impaired left ventricular function. In diabetic CRT patients the addition of an ICD reduces the risk of all-cause mortality mostly seen in the first six years. These findings might implicate the relevance of adding an ICD to CRT even at a higher ejection fraction in those with severe comorbidities such as diabetes.